If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 4 = 26 Reorder the terms: 4 + 4n = 26 Solving 4 + 4n = 26 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4n = 26 + -4 Combine like terms: 4 + -4 = 0 0 + 4n = 26 + -4 4n = 26 + -4 Combine like terms: 26 + -4 = 22 4n = 22 Divide each side by '4'. n = 5.5 Simplifying n = 5.5
| 2.1x+1.15y=2.30 | | 500=200+1.75 | | 24p^2-16p=0 | | 8-18x^2=0 | | 1x^2-16=0 | | -3(1-3b)-12=12 | | 5x+3+2x-4= | | -8x-17=3x-105 | | e=5n+8 | | 5x^2+8=4x^2-6x | | 25=-16t^2+35t+5 | | 8x^2=980 | | -3(3b+1)-12=12 | | (b^6c^2)-8= | | .20*65=x | | s+s+325000=550000000 | | s+s+32500=550000000 | | 2(2+2y)=19-3y | | s+s+325=550 | | -15-3x=-7x+45 | | F*0=6*0-1 | | 5xn-20=8 | | 14=1.5(7) | | 6(6+68)= | | n+36=56 | | 12s-12=9s-8 | | 6x+6=4x-2 | | 60x-60=144 | | n*5=95 | | 4m^2-227m-40=0 | | n-2=180 | | 3x-2=6+4x |